2020
DOI: 10.3390/antibiotics9090589
|View full text |Cite
|
Sign up to set email alerts
|

Is Only Clarithromycin Susceptibility Important for the Successful Eradication of Helicobacter pylori?

Abstract: Resistance to clarithromycin and other antibiotics included in the eradication regimen, such as amoxicillin and metronidazole, is important for Helicobacter pylori (H. pylori) eradication. The aim of this study was to investigate the correlation between the results of antimicrobial susceptibility testing and the eradication rate, as well as to understand the importance of antimicrobial susceptibility testing in H. pylori eradication. We retrospectively reviewed the electronic medical records of 1862 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…A total of 31 studies reported data on therapeutic outcomes [ 31 - 61 ]. Of these, 19 studies compared the cure rates between culture-tailored and empiric therapies [ 31 - 42 , 52 - 58 ], whilst only the cure rates of tailored therapies were reported in the remaining 12 studies [ 43 - 51 , 59 - 61 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 31 studies reported data on therapeutic outcomes [ 31 - 61 ]. Of these, 19 studies compared the cure rates between culture-tailored and empiric therapies [ 31 - 42 , 52 - 58 ], whilst only the cure rates of tailored therapies were reported in the remaining 12 studies [ 43 - 51 , 59 - 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the attempt to guide first-line therapy for H. pylori failed in 1 of every 5 infected patients. On the other hand, when the culture was attempted in unselected naïve patients who underwent upper endoscopy, the antibiotic susceptibility testing was achieved in only 247 (13.3%) of 1862 cases [ 59 ]. Based on all these observations, tailoring first-line therapy seems to be impractical in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…In this approach, the cellular uptake is quantified by measuring the reduction of the inhibitor concentration in the external culture medium, and numerous detection methods were shown to be suitable: LC-MS and UV absorption, as well as the inhibition of the target enzyme. The method has been confirmed using metronidazole, an antibiotic used in H. pylori therapies (e.g., Min Kim et al, 2020;Olmedo et al 2020).…”
Section: Discussionmentioning
confidence: 95%
“…Hadacidin is a structural analogue of one of the AdSS substrates, aspartate, and is a potent inhibitor of this enzyme (Iancu et al 2006;Bubić et al 2018). Metronidazole is an antibiotic efficiently used in therapy against H. pylori (e.g., Min Kim et al;Olmedo et al 2020), and it is used in this study as a positive control of the cellular uptake 1 3…”
Section: Methodsmentioning
confidence: 99%
“…The success rate of culture was evaluated in different settings of clinical practice, from before first-line therapy to following more treatment failures. In a large Korean study, where the prevalence of H. pylori infection in the general population is high, antibiotic susceptibility testing was achieved in only 247 (13.3%) of 1862 unselected naïve patients undergoing upper endoscopy in whom bacterial culture was attempted [ 23 ]. This would mean that bacterial culture was useless in as many as 9 of every 10 cases who underwent upper endoscopy.…”
Section: Introductionmentioning
confidence: 99%